IMPLEMENTASI SRATEGI PEMBELAJARAN UNTUK MENINGKATKAN BELAJAR MENGAJI ANAK BERKEBUTUHAN KHUSUS DI TK INKLUSI PAS BAITUL QUR’AN NGABAR PONOROGO - Khoirul Ummah; Happy Susanto; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2021)
Children with speech delay special needs are children who experience barriers to communication. ABK speech delay requires special treatment in learning, including in learning the Koran. Learning the Koran is a difficult thing for speech delay ABK because the most important thing in reciting is that someone can pronounce the hijaiyah letters properly and correctly. This study aims to find out how the implementation of learning strategies in PAS Baitul Qur'an Ngabar Inclusion Kindergarten, researchers use a qualitative approach and the type of research used is a case study, to obtain data in this study using observation, documentation, and interview techniques. This study obtained the following results: to improve learning the Koran the teacher applied a strategy with several stages, the first stage was the introduction of hijaiyah letters with flash card learning media, then identification of hijaiyah letters, followed by mouth motor imitation or imitating what the teacher said, and the last stage is to label hijaiyah letters.